Prevalence, Pathophysiology, Diagnostic Modalities, and Treatment Options for Dysphagia in Critically Ill Patients. (December 2020) - Brodsky, Martin B.; Nollet, Joeke L.; Spronk, Peter E.; González-Fernández, Marlís
Abstract : Abstract: Postextubation dysphagia may impose a substantial burden on intensive care unit patients and healthcare systems. Approximately 517, 000 patients survive mechanical ventilation during critical care annually. Reports of postextubation dysphagia prevalence are highly variable ranging between 3% and 93%. Of great concern is aspiration leading to the development of aspiration pneumonia when patients resume oral feeding. Screening for aspiration with a water swallow test has been reported to be positive for 12% of patients in the intensive care unit after extubation. This review aims to increase awareness of postextubation dysphagia and provide an updated overview of the current knowledge regarding prevalence, pathophysiology, diagnostic modalities, and treatment options.